Gynecologic oncology care in the world of accountable care organizations - K.M. Dorney; S.K. Rao; R.C. Sisodia; M.G. del Carmen (Elsevier, 2019)
Accountable Care Organizations (ACOs) are an example of alternative payment models that are becoming increasingly common in our healthcare system. ACOs focus on increasing value through cost reduction and improved outcomes, and historically focus on Medicare patients within primary care practices. As ACOs grow, attention will likely turn to costly subspecialty care as an area for improvement and standardization. This brief communication addresses the potential benefits and consequences of ACOs on Gynecologic Oncologists and for patients with gynecologic malignancies. Keywords: Accountable Care Organizations (ACOs), Value, Quality, Cost